Drying properties of bloodstains on common indoor surfaces - Ramsthaler, Frank; Schmidt, Peter; Bux, Roman; Potente, Stefan; Kaiser, Cristina; Kettner, Mattias (International journal of legal medicine, 2012)
When blood reaches an extracorporeal surface, a drying process is initiated. Properties of this drying process may be crucial for the correct assessment of case-specific time lapses, however, there is a lack of systematic studies concerning the drying times of blood. We present a study on drying properties of small blood droplets with a standardized size of 25 μl (resembling droplets originating from pointed and sharp objects, e.g. the tip of a knife) under different environmental conditions to elucidate the effect of different ambient temperatures, indoor surfaces and anticoagulant treatment. As a rule of thumb, wiping a typical small blood droplet will not lead to a macroscopically visible smear after a time period of approximately 60 min (timemin = 45 min; timemax = 75 min) at an average room temperature of 20 °C. Alteration of the ambient temperature has a remarkable effect, as the time needed for the drying process leading to wipe resistance of the droplets decreases to 30 min (timemin) at an ambient temperature of 24 °C, and is prolonged up to >120 min (timemax) at an ambient temperature of 15 °C. As for the surface materials in our study, significant differences in drying periods were only found between wood and linoleum (80th percentile 45 vs. 75 min). Treatment with anticoagulants did not influence extracorporeal drying times. In synopsis, the present study shows that ambient temperature is a major determinant of the drying process of blood droplets and should always be documented accurately and continuously on a crime scene. In certain situations, an estimation of the time elapsed since bloodstain origination may be of importance to answer questions related to the time course of actions. However, further systematic studies are needed to clarify the effect of other properties such as droplet size, humidity, or evaporation.